BEKAL KEMAMPUAN DASAR DAN STRATEGI UNTUK BIDANG MULTIMEDIA KESIAPAN KERJA DAN USAHA TINGKAT SMK (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
Multimedia is a technology-based interactive media to convey information through both print andelectronic media. Multimedia that is often used and seen is using electronic media such as video because it iseasy to understand. There are 5 elements of multimedia, namely text, images, audio, video and animation. Ifthese five elements are put together, a very good multimedia product will be created, such as movies and soon. This training is carried out in order to increase students' knowledge about multimedia for provision whenthey graduate from school to work in companies or open businesses in the multimedia field. The method usedin this activity is the lecture method, namely providing an explanation or presentation of material aboutmultimedia to students and also the discussion method, namely a question and answer session after thelecture method is carried out, here students ask questions related to the material and the presenters provideanswers according to the questions asked. The result of this activity is that students understand more aboutthe differences between multimedia communication and multimedia content production as well as theelements of multimedia. Students were very enthusiastic in participating in this activity because a lot ofknowledge was gained during the activity.